Modelling, simulation and dynamics of a synch-rotor aircraft - Bertolani, G.; De Angelis, E.L.; Giulietti, F.; Rossetti, G. (My University, 2020)
This paper presents a detailed modelling, control system design, and numerical simulation of a rotary wing aircraft with two synchronised rotors. Following the derivation of the complete non-linear 6 DoF equations, a nested loop control architecture made of attitude stabilisation and trajectory tracking is designed after a linearisation process. Numerical simulation and performance analysis are carried out. Results concerning hovering and forward flight, relevant from the perspective of practical applications are presented and discussed. The synch-rotor configuration appears suitable and effective for application where Unmanned Aerial Systems are foreseen such as environment monitoring, aerial photogrammetry, and load transportation.